THE INFLUENCE OF VISUAL ELEMENTS AND EASE OF USE ON PURCHASE DECISIONS THROUGH TIKTOK SHOP AMONG GEN Z - Kaseger, Enjelie; Worang, Frederik G.; Gunawan, Emilia (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
This study aims to test the influence of visual elements and ease of use on purchase decision partially and simultaneously. Data were collected through a questionnaire method with a population of 103.689 and by using the Slovin formula, 99,90 samples were obtained, however, the sample was rounded up to 100. The result indicates that both Visual Elements and Ease of Use play crucial roles in influencing purchase decisions. When analyzed simultaneously, these factors significantly impact how consumers decide to buy products. Partially, each factor also shows a distinct influence on purchase decisions. Visual elements significantly influence purchase decisions by enhancing the visual appeal and communication of video content, making products more enticing to Gen Z users. Meanwhile, ease of use of TikTok Shop significantly affects purchase decisions, as Gen Z users prefer intuitive and user-friendly technology. A seamless and hassle-free shopping experience increases user satisfaction and the likelihood of purchase.   Keywords: Visual Elements, Ease of Use, Purchase Decision, Social Media Marketing